Bovine Epithelial in vitro Infection Models for Mycoplasma bovis - Josi, Christoph; Bürki, Sibylle; Stojiljkovic, Ana; Wellnitz, Olga; Stoffel, Michael H.; Pilo, Paola (Frontiers in Cellular and Infection Microbiology, 2018)
Mycoplasma bovis causes bovine mycoplasmosis. The major clinical manifestations are pneumonia and mastitis. Recently an increase in the severity of mastitis cases was reported in Switzerland. At the molecular level, there is limited understanding of the mechanisms of pathogenicity of M. bovis. Host-pathogen interactions were primarily studied using primary bovine blood cells. Therefore, little is known about the impact of M. bovis on other cell types present in infected tissues. Clear in vitro phenotypes linked to the virulence of M. bovis strains or tissue predilection of specific M. bovis strains have not yet been described. We adapted bovine in vitro systems to investigate infection of epithelial cells with M. bovis using a cell line (MDBK: Madin-Darby bovine kidney cells) and two primary cells (PECT: bovine embryonic turbinate cells and bMec: bovine epithelial mammary gland cells). Two strains isolated before and after the emergence of severe mastitis cases were selected. Strain JF4278 isolated from a cow with mastitis and pneumonia in 2008 and strain L22/93 isolated in 1993 were used to assess the virulence of M. bovis genotypes towards epithelial cells with particular emphasis on mammary gland cells. Our findings indicate that M. bovis is able to adhere to and invade different epithelial cell types. Higher titers of JF4278 than L22/93 were observed in co-cultures with cells. The differences in titers reached between the two strains was more prominent for bMec cells than for MDBK and PECT cells. Moreover, M. bovis strain L22/93 induced apoptosis in MDBK cells and cytotoxicity in PECT cells but not in bMec cells. Dose-dependent variations in proliferation of primary epithelial cells were observed after M. bovis infection. Nevertheless, an indisputable phenotype that could be related to the increased virulence towards mammary gland cells is not obvious.